THE SIGNIFICANCE OF ENTREPRENEURIAL LEADERSHIP TOWARDS MALAYSIAN SCHOOL PERFORMANCE: MEDIATOR BY EMPOWERMENT - Norhisham Mohd Kasim; Mohd Nazri Zakaria (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
School performance is a main agenda in school organization to achieving the vision and mission as well as the main objectives of the Ministry of Education. Issues on performance in the context of school organization are based on leadership management. The main issues highlighted are based on leadership in achieving the ultimate goal of the Ministry of Education (MOE). This study examines the leadership among the headmasters and principals in schools in improving the performance of schools in Malaysia. From the concept of leadership, the leadership that forms the leadership of entrepreneurship among teachers in every school leader plays an important role in the education system to deal with changes and challenges. Entrepreneurial leadership is a leader who is classified to achieve the same goal of using entrepreneurial behavior. Hence, this study focuses for entirely on entrepreneurial leadership relationship with school performance in Malaysia. Supported by the Model Leader Member Exchange theory, this study proposes a framework by outlining the factors that exist in entrepreneurial leadership and empowering. A total of 171 school administrators from public schools were participated in this study. Data for this study variables were collected through a self-administered survey. Structural Equation Modeling (SEM) is the main statistical technique used in this study. The findings show that some variables such as entrepreneurial leadership and empowerment are significant in relation to school performance. The findings will contribute to future research that researchers can research deeply on the performance of public or private schools in Malaysia.